PRIMEIRO RELATO DE Xanthomonas sp. CAUSANDO MANCHA FOLIAR EM FALSA SERRALHA EM MATO GROSSO DO SUL - CAVALCANTI, Vittor Gomes; COSTA, Brenda Fernandes da; GRAICHEN, Felipe André Sganzerla; BLANCO, Neder Henrique Martinez; DA SILVA, Talísia da Souza; MENDONÇA, Cristiane Gonçalves (ANAIS DO ENIC, 2026)
.